Quantum-Spacetime Scenarios and Soft Spectral Lags of the Remarkable GRB130427A. (20th January 2014) - Amelino-Camelia, Giovanni; Fiore, Fabrizio; Guetta, Dafne; Puccetti, Simonetta
Abstract : We process the Fermi LAT data on GRB130427A using the Fermi Science Tools, and we summarize some of the key facts that render this observation truly remarkable. We then perform a search of spectral lags, of the type that has been of interest for its relevance in quantum-spacetime research. We do find some evidence of systematic soft spectral lags: when confining the analysis to photons of energies greater than 5 GeV there is an early hard development of minibursts within the burst. The effect is well characterized by a linear dependence, within such a miniburst, of the detection time on energy. We also observe that some support for these features is noticeable also in earlier Fermi-LAT GRBs. Some aspects of the comparison of these features for GRBs at different redshifts could be described within a quantum-spacetime picture, but taking into account results previously obtained by other studies we favour the interpretation as intrinsic properties of GRBs. Even if our spectral lags do turn out to have astrophysical origin their understanding will be important for quantum-spacetime research, since any attempt to reveal minute quantum-spacetime-induced spectral lags evidently requires a good understanding of intrinsic mechanisms at the sources that can produce spectral lags.